Analyzing the Anthropogenic Allee Effect in cycad (Encephalartos species) populations in South Africa: an evaluation of illegal trade and conservation policy - Earle, Sasha (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2019)
South Africa is a country known for rich biodiversity and ecosystems across the land and seascape. South Africa is one of the global hotspots for cycad diversity. Cycads are known to be the world's most threatened plant species; declining in South Africa at a rapid pace, with threat of extinction in the wild. The main factor being harvesting from the wild for private collections. Rare cycad species' are especially sought after by collectors. Economic theory assumes that the exploitation of a species is unlikely to result in extinction due to the increasing costs of finding the last few individuals of a species. However, the theory of the Anthropogenic Allee Effect (AAE) suggests that if consumers place a disproportionate value on a rare species', a cycle may result whereby increased exploitation decreases population size, increasing the value of the species and, consequently, leading to its extinction in the wild. This hypothesis was tested for 37 Encephalartos species using data collected on wild populations, auction prices and the IUCN Red List status for the year 2010. It was hypothesised that an AAE was present within Encephalartos species, as three species have already gone extinct in the wild. The price per centimetre was positively correlated to the rarity of the species and the price per centimetre was negatively correlated to the wild population size. The results suggest a trend of an AAE for the year 2010. Adequate conservation policies are needed to reduce the effects of demand on illegal harvesting and prevent extinction in the wild. The effect of rarity needs to be taken into account to ensure successfulness of such policies. The most recent conservation policy implemented to protect cycads in South Africa is the Strategy and Action for the Management of Cycads in South Africa, which was introduced in 2016. The successfulness of this policy cannot, however, be analysed due to a lack of census data following its implementation.
Keywords: Allee effect; Cycads -- Conservation -- South Africa; Botany, Economic -- South Africa; Rare plants -- South Africa; Endangered plants -- South Africa; Wild plant trade -- Law and legislation -- South Africa